2003
DOI: 10.1021/ie0300981
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Process for the Conversion of Halon 1211 (CBrClF2) to Halon 1301 (CBrF3) and CFC 13 (CClF3)

Abstract: This paper reports the catalytic pyrolysis of CBrClF2 over γ-Al2O3 and β-AlF3 in a plug-flow reactor operated at atmospheric pressure and within the temperature window of 523−673 K. The results indicate a very high conversion of halon 1211, in excess of 90% for γ-Al2O3 and 60−80% for β-AlF3, over the entire temperature range. Halon 1301 (CBrF3) and CFC 13 (CClF3) are the main pyrolysis products, although their yields vary with temperature and catalyst type. If accepted by regulators, this process offers a reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…As fluorocarbons possess valuable C–F bonds, they are attractive as chemical feedstock for production of useful products. In response to this potential, we developed a thermal process to convert fluorocarbons to useful products, also based on the reaction of these compounds with methane. Catalysts have also been combined with thermal reactions with a similar aim …”
Section: Introductionmentioning
confidence: 99%
“…As fluorocarbons possess valuable C–F bonds, they are attractive as chemical feedstock for production of useful products. In response to this potential, we developed a thermal process to convert fluorocarbons to useful products, also based on the reaction of these compounds with methane. Catalysts have also been combined with thermal reactions with a similar aim …”
Section: Introductionmentioning
confidence: 99%
“…During the catalytic conversion of Halon 1211 (CBrClF 2 ) to Halon 1301 (CBrF 3 ) and CFC 13 (CClF 3 ), higher activity was observed over Al 2 O 3 compared with AlF 3. For the used Al 2 O 3 catalyst, an aluminum fluoride/aluminum hydroxide hydrate phase in the X-ray diffraction (XRD) pattern was detected. It seems probable that a new phase was formed on the surface of the reactor following the introduction of O 2 , which plays a major role in enhancing the rate of dismutation of CHClF 2 and subsequent formation of CHF 3 .…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that some phases of alumina can catalyze CFC and halon Cl/F exchange or dismutation reactions 29–32. The reactor used in the present investigation was made of α‐alumina.…”
Section: Chemical Kinetic Modelingmentioning
confidence: 99%